Strategi Promosi Perpustakaan Mini Dalam Menumbuhkan Budaya Literasi Anak Usia Dini di Raudhatul Athfal Am-Mentari Kota Jambi - Dewanti Apriliana; Sukarno Sukarno (SOKO GURU: Jurnal Ilmu Pendidikan, 2025)
This study aims to describe and analyze the promotional strategies implemented by the mini library at Raudhatul Athfal (RA) AM-Mentari in Jambi City to foster a culture of literacy in early childhood. The background to this research stems from the importance of laying the foundation for early literacy and the strategic role of school libraries as learning resource centers. The research method used was a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews with the principal, teachers, and library staff, and documentation of promotional activities. The subjects of this study focused on the implementation of programs and activities designed to increase reading interest among children at RA AM-Mentari. The results indicate that effective promotional strategies at RA AM-Mentari include three main approaches: (1) Interactive Program Strategy, through routine storytelling activities, coloring competitions, and guided reading habits in the classroom; (2) Environmental Strategy, by creating attractive, comfortable, and accessible reading corners for children; and (3) Partnership Strategy, through active parental involvement and internal collaboration between teachers. In conclusion, a promotional strategy that is fun, consistent, and integrated into the daily curriculum has proven effective in engaging early childhood with books, thereby gradually fostering a sustainable literacy culture within the school environment.